1993
DOI: 10.2214/ajr.161.4.8396848
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma: MR imaging findings in 34 patients.

Abstract: OBJECTIVE.MR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(116 citation statements)
references
References 3 publications
5
101
0
2
Order By: Relevance
“…Presence of triple signal intensity on T2WI was an useful criteria as it was statistically significant (p value <0.05). This triple signal intensity has been described in synovial sarcomas by Jones et al 9 . Sundaram et al 10 had also found hyper-& hypointense signal intensity in 3 cases of MFH.…”
Section: Mrisupporting
confidence: 70%
“…Presence of triple signal intensity on T2WI was an useful criteria as it was statistically significant (p value <0.05). This triple signal intensity has been described in synovial sarcomas by Jones et al 9 . Sundaram et al 10 had also found hyper-& hypointense signal intensity in 3 cases of MFH.…”
Section: Mrisupporting
confidence: 70%
“…The differential diagnosis of the tumor includes; synovial sarcoma and malignant fibrous histiocytoma which has more recently classified as pleomorphic undifferentiated sarcoma. Synovial sarcomas showed typical intermixed areas of low, intermediate and high signal intensity defining as 'triple sign' on T2 weighted images 8 9 . We found a mean ADC value of 0.98 ± 0.06 x10 -3 mm 2 /sec which is highly suspicious for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…MRI often shows a heterogeneous appearance, with low signal intensity on T1-weighted images, high signal intensity on T2-weighted images, and contrast enhancement [1]. Unlike GCTTS, approximately 44% of synovial sarcomas have foci of hemorrhage observed on MR images, but both entities frequently are found in close proximity to a joint [9]. Epithelioid sarcoma is another malignant lesion that should be considered in the differential diagnosis.…”
Section: Discussion and Treatmentmentioning
confidence: 99%